The Role of the Global Solar UV Index for Sun Protection of Children in German Kindergartens - Gefeller, Olaf; Mathes, Sonja; Uter, Wolfgang; Pfahlberg, Annette Bettina (Children, 2022)
More than twenty‐five years ago, the Global Solar UV index (UVI) was introduced as a simple means of visualizing the intensity of ultraviolet radiation and to alert people to the need for sun protection. In our survey, among directors of 436 kindergartens in southern Germany we investigated the level of awareness and knowledge about the UVI as well as the practical consequences for sun protection in kindergartens. Less than half of the directors (n = 208, 47.7%) had ever heard of the UVI, and only a small minority of them (n = 34, 8.7%) used the daily UVI information to adapt sun protective measures in their kindergartens. Detailed knowledge about the UVI was a rarity among the respondents. The proportion of respondents with self‐perceived detailed UVI knowledge was five times higher than the actual knowledge assessed by an in‐depth structured interview using open‐ended questions about the UVI (14.2% vs. 2.8%). No clear relationship between UVI awareness, knowledge, and use and directors’ age and gender was found. The UVI‐related variables also showed no association with directors’ knowledge of risk factors for skin cancer and their attitudes towards tanned skin. Overall, the results paint a sobering picture regarding the penetration of the UVI into sun protection policies of German kindergartens. Future public health campaigns should aim to increase the awareness and understanding of the UVI as well as its relevance for sun protection of children.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Health attitudes; Health knowledge; Skin cancer; Sun protection; Ultraviolet radiation; UV index